Genetic evidence that the ovo locus is involved in Drosophila germ line sex determination. - Oliver, B.; Pauli, D.; Mahowald, A.P. (Genetics, 1990)
Zygotically contributed ovo gene product is required for the survival of female germ cells in Drosophila melanogaster. Trans-allelic combinations of weak and dominant ovo mutations (ovoD) result in viable germ cells that appear to be partially transformed from female to male sexual identity. The ovoD2 mutation is partially suppressed by many Sex-lethal alleles that affect the soma, while those that affect only the germ line fail to interact with ovoD2. One of two loss-of-function ovo alleles is suppressed by a loss-of-function Sex-lethal allele. Because ovo mutations are germ line dependent, it is likely that ovo is suppressed by way of communication between the somatic and germ lines. A loss-of-function allele of ovo is epistatic to germ line dependent mutations in Sex-lethal. The germ line dependent sex determination mutation, sans fille, and ovoD mutations show a dominant synergistic interaction resulting in partial transformation of germ line sexual identity. The ovo locus appears to be involved in germ line sex determination and is linked in some manner to sex determination in the soma.